TOURISM: ON THE EXAMPLE OF THE SHRINES OF THE FERGHANA (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article attempts to show the significance and role of shrines, as well as shrines that further enrich the unique tourist attraction of the Ferghana Valley. Ferghana shrines are also important for their antiquity, value for the local population and special value for domestic tourism.